Adaptive Models for the Energy Efficiency of Building Envelopes - Milardi, Martino (Journal of Technology Innovations in Renewable Energy, 2018)
The debate on energy efficiency in buildings has already established the strategic role of the envelope to achieve the control objectives of consumption and housing quality. The study shows, it ranks in the innovative experimentation scenario, following the directions of the regulations 2010/31/EU (EPBD 2) and its objective is the realization of a building envelope "adaptive", characterized by the ability to dynamically respond to stress from the environmental context with which it relates. The experiment aimed at perfecting a model of intervention that can guide the design choices towards elements that make up the building envelope, characterized by a strong interactive-adaptive component. This is based on the combination of: layers of innovative envelope, systems using RES and SMART management requirements of the system, with a focus on intelligent control energy flows between external/internal and adaptive performance of the layers. The mode of "deferred layering" in relation to the orientation of the building and to climate periods, while for the control of wrap responses subjected to environmental stress, the research adopts BEMS & BIM systems and other related criteria will be defined. The experiment aims to satisfy the requirements to improve the energy performance of buildings by reducing the impacts (emissions), through the development of a technical system. The results obtained from inspections in progress, show that the constituent layers that envelope react in a synergistic way and adapted to different climatic conditions, ensuring high-quality performance, in line with the energy efficiency targets established by regulatory standards.